CARE OF GUILLAIN-BARRé SYNDROME AFTER ICU DISCHARGE. Issue 10 (9th September 2014) - Howard, Robin; Sanctuary, Thomas; Steier, Joerg; Hart, Nick
Abstract : Respiratory insufficiency occurs in 25% of patients with GBS and major complications are common. In the UK, the mortality rate in ICU is 7.7% but the in-hospital mortality rate after ICU step-down is 16.7%. The cause of this alarmingly high rate is unclear but delayed weaning and long-term ventilatory support are critical to outcome. We present a review of 20 patients managed in a tertiary referral centre over 12 years. The mean age of patients was 59.3 years with a marked male predominance. All had tracheostomy at the time of transfer. The duration of mechanical ventilation between the onset and the time of transfer varied between 45–489 days. The time from admission to decanulation varied from 1–118 days. 19 patients were successfully weaned from invasive ventilatory support, 5 required non-invasive (NIV) nocturnal support for 10–225 days, one has continued to use ongoing nocturnal NIV and one patient died. 19 patients were successfully discharged. This series argues that the ongoing care of patients with GBS who have been discharge from ICU requires meticulous and specialised expertise. Failure to provide such support may account for the disturbingly high UK mortality after discharge from intensive care.